2012
DOI: 10.1590/s0100-879x2012007500082
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bartonella spp bacteremia with Chagas cardiomyopathy, endocarditis and arrythmias in patients from South America

Abstract: Infection with Bartonella spp may cause cardiac arrhythmias, myocarditis and endocarditis in humans. The aim of the present study was to evaluate a possible association between Bartonella spp bacteremia and endocarditis, arrhythmia and Chagas cardiomyopathy in patients from Brazil and Argentina. We screened for the presence of bacterial 16S rRNA in human blood by PCR using oligonucleotides to amplify a 185-bp bacterial DNA fragment. Blood samples were taken from four groups of subjects in Brazil and Argentina:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition, Correa et al . reported that the risk of Bartonella DNA bloodstream infection was 45 times higher in arrhythmic patients from Brazil or Argentina when compared to controls [ 31 ]. Our results expand the current understanding about Bartonella species infection in humans in Brazil by reinforcing the ecological role of cats and ectoparasites in the transmission of Bartonella .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Correa et al . reported that the risk of Bartonella DNA bloodstream infection was 45 times higher in arrhythmic patients from Brazil or Argentina when compared to controls [ 31 ]. Our results expand the current understanding about Bartonella species infection in humans in Brazil by reinforcing the ecological role of cats and ectoparasites in the transmission of Bartonella .…”
Section: Discussionmentioning
confidence: 99%
“…Another series of 46 culture-negative endocarditis patients from the city of São Paulo used PCR to investigate Bartonella spp. in blood and found 13 (28%) patients with positive results ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same direction, detection of other agents such as bacteria in myocardial tissue and blood of chagasic patients with cardiomyopathy has already been reported [13,14]. The finding of co-infection in chagasic DCM may turn the understanding of Chagas' disease pathogenesis even more difficult, considering its multifactorial feature and not well understood interactive pathways [38].…”
Section: Co-infections and Chagas' Heart Diseasementioning
confidence: 95%
“…Recently, the potential role of co-infections on pathogenesis of Chagas' heart disease has been debated [13,14]. Chagas' disease is a common and endemic cause of acquired inflammatory DCM especially in Latin America accepted as caused by the protozoa Trypanosoma cruzi [15,16], however, doubts also persist regarding pathogenesis of chagasic DCM.…”
Section: Introductionmentioning
confidence: 99%